2011 Proceedings of IEEE Southeastcon 2011
DOI: 10.1109/secon.2011.5752942
|View full text |Cite
|
Sign up to set email alerts
|

Survey of popular robotics simulators, frameworks, and toolkits

Abstract: Robotic simulators, frameworks, and related toolkits are very important in today's research community. The need to accurately simulate movements, algorithms, and interactions with the real world is quickly becoming a major research focus as humans and robots interact in more situations and differently than ever before. This is a survey of popular robotics simulators and some of the main frameworks and toolkits that are used to help bring robotics simulations to a one-to-one relationship with real-world interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 15 publications
0
25
0
7
Order By: Relevance
“…This fact implies that system (1) in closed loop with (6) achieves that ( , , ) → ( * , * , * ) when → ∞. Likewise, according to the stability analysis carried out in [98], it was shown that = 1/ 3 and ] * must be greater than 0.…”
Section: Control At the Highest Hierarchical Level: Mechanicalmentioning
confidence: 89%
See 1 more Smart Citation
“…This fact implies that system (1) in closed loop with (6) achieves that ( , , ) → ( * , * , * ) when → ∞. Likewise, according to the stability analysis carried out in [98], it was shown that = 1/ 3 and ] * must be greater than 0.…”
Section: Control At the Highest Hierarchical Level: Mechanicalmentioning
confidence: 89%
“…As a matter of fact, diverse applications of WMRs have been reported in many fields like handling explosives or radioactive materials/waste, planetary and maritime exploration, mining and petrochemical industry, medicine, agriculture, home, and entertainment, among others [4][5][6][7]. On one hand, control of WMRs is not an easy task since their models are nonlinear and are subject to nonholonomic constraints [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Harris et-al., [15] gives a good outline of the available simulators, frameworks and tool-kits. The authors suggest that most simulators are not well documented (for anything but Windows environments), have no sensors, or offer no possibilities for the integration of new robots, sensors, etc.…”
Section: B Simulationmentioning
confidence: 99%
“…The ROS software platform [1] is based around architectural principles common to many robotic software frameworks [2]: the abstraction of both hardware and software interfaces to facilitate code reuse and composition.…”
Section: A Rosmentioning
confidence: 99%